Effect of Family Support, Learning Strategies, And Lecturer Professional Competence Through Self-Regulated Learning Mediator on Online Learning Motivation of FAI PTKIS Students Kopertais III Yogyakarta - Siti Khoiriyah; Akif Khilmiyah; Aris Fauzan (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2021)
This study aims to determine the effect of family support, learning strategies and lecturers' professional competence through self-regulated learning mediator on the online learning motivation of students of the Faculty of Islamic Religion (FAI) PTKIS III (UMY and UAD). The research analysis uses the Structural Equation Model (SEM) with the assistance of AMOS program. The results show that there is a significant effect of family support, learning strategies and lecturers' professional competence through self-regulated learning mediator on online learning motivation. Based on the results of Confirmatory Factor Analysis (CFA), it is found that after the Modification Indices, the criteria of Goodness of Fit is met with a Chi-square value of 56,760, Sig-Probability 0,94, CMIN/DF 1,290, GFI 0,963, CFI 0,983, TLI 0,983, NFI 0,952, RMSEA 0.032 and RMR 0.124. From these results, it is indicated that the model is fit. The implication of this research for the community is to increase motivation to learn online, it requires family emotional support, learning strategies by creating a high and fun learning strategies and good learning programs.